Cytotoxicity of gamma irradiated aflatoxin B1 and ochratoxin A. Issue 3 (4th March 2019) - Domijan, Ana-Marija; Marjanović Čermak, Ana Marija; Vulić, Ana; Tartaro Bujak, Ivana; Pavičić, Ivan; Pleadin, Jelka; Markov, Ksenija; Mihaljević, Branka
Abstract: Toxicity of gamma irradiated mycotoxins aflatoxin B1 (AFB1 ) and ochratoxin A (OTA) was investigated in vitro . AFB1 and OTA stock solutions (50 mM, in methanol) were gamma irradiated (5 and 10 kGy) and non-irradiated and irradiated mycotoxins solutions were tested for cytotoxicity on Pk15, HepG2 and SH-SY5Y cell lines (MTT assay, 1–500 μM concentration range; 24 h exposure). Degradation of mycotoxin molecules was examined by liquid chromatography tandem mass spectrometry (HPLC-MS/MS). AFB1 and OTA radiolytic products were less toxic than the parent mycotoxins to all of the tested cell lines. Gamma irradiation even at 5 kGy had effect on AFB1 and OTA molecules however, this effect was dependent on chemical structure of mycotoxin. Since gamma irradiation at low dose reduced initial level of both mycotoxins, and gamma irradiated mycotoxins had lower toxicity in comparison to non-irradiated mycotoxins, it can be concluded that gamma irradiation could be used as decontamination method.